2011
DOI: 10.1002/em.20650
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and nucleotide excision repair capacity in healthy individuals

Abstract: Interindividual differences in DNA repair capacity (DRC) represent an important source of variability in genome integrity and thus influence health risk. In the last decade, DRC measurement has attracted attention as a potential biomarker in cancer prediction. Aim of the present exploratory study was to characterize the variability in DNA damage and DRC on 100 healthy individuals and to identify biological, lifestyle, or genetic factors modulating these parameters. The ultimate goal was to obtain reference dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 66 publications
3
32
0
Order By: Relevance
“…In the present study, XPD genotype did not influence the outcome of DNA damage assessed by SCGE or DNA repair as assessed by 8-oxo-dG, though it should be noted that 8-oxo-dG is not a specific product of the protein coded from XPD. These results are consistent with a recent study that reported that endogenous DNA damage and (+)-anti-benzo[a]-pyrene-7,8-dihydrodiol-9,10-epoxide-induced DNA repair capacity in PBMCs from a healthy population did not correlate with XPD751 genotypes [75]. …”
Section: Discussionsupporting
confidence: 93%
“…In the present study, XPD genotype did not influence the outcome of DNA damage assessed by SCGE or DNA repair as assessed by 8-oxo-dG, though it should be noted that 8-oxo-dG is not a specific product of the protein coded from XPD. These results are consistent with a recent study that reported that endogenous DNA damage and (+)-anti-benzo[a]-pyrene-7,8-dihydrodiol-9,10-epoxide-induced DNA repair capacity in PBMCs from a healthy population did not correlate with XPD751 genotypes [75]. …”
Section: Discussionsupporting
confidence: 93%
“…We therefore also investigated whether DNA repair parameters assayed in this study are affected by gender. Gender effects on the level of endogenous SSBs have previously been reported in human PBMCs (Hofer et al , 2006; Slyskova et al , 2011), and indications of gender effects on DSBR were reported in a small study of 20 study subjects (Mayer et al , 1991). Several reports have suggested gender effects on other DNA repair pathways, primarily NER (Wei et al , 1993; Slyskova et al , 2011; Uppstad et al , 2011).…”
Section: Introductionmentioning
confidence: 77%
“…Higher levels of endogenous SSBs have been reported in PBMCs from men compared with women (Hofer et al , 2006; Slyskova et al , 2011). Men had higher levels of DNA damage than women in these studies including approximately 100 study subjects.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations